2017
DOI: 10.1042/cs20170010
|View full text |Cite
|
Sign up to set email alerts
|

VMP1-related autophagy induced by a fructose-rich diet in β-cells: its prevention by incretins

Abstract: The aim of the present study was to demonstrate the role of autophagy and incretins in the fructose-induced alteration of β-cell mass and function. Normal Wistar rats were fed (3 weeks) with a commercial diet without (C) or with 10% fructose in drinking water (F) alone or plus sitagliptin (CS and FS) or exendin-4 (CE and FE). Serum levels of metabolic/endocrine parameters, β-cell mass, morphology/ultrastructure and apoptosis, vacuole membrane protein 1 (VMP1) expression and glucose-stimulated insulin secretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…It should be noted, however, that GLP-1 induced changes can vary depending on the underling mechanism of stress. For example, while usually promoting autophagy, treatment with GLP-1 analogs in a high fructose fed rat model resulted in apparent inhibition of β-cell autophagy, and increase in β-cell mass and function ( 95 ). The underlying mechanisms and downstream molecular mediators through which GLP-1 influences autophagy remain to be better characterized.…”
Section: Chronic Effects Of Glp-1 In β-Cellsmentioning
confidence: 99%
“…It should be noted, however, that GLP-1 induced changes can vary depending on the underling mechanism of stress. For example, while usually promoting autophagy, treatment with GLP-1 analogs in a high fructose fed rat model resulted in apparent inhibition of β-cell autophagy, and increase in β-cell mass and function ( 95 ). The underlying mechanisms and downstream molecular mediators through which GLP-1 influences autophagy remain to be better characterized.…”
Section: Chronic Effects Of Glp-1 In β-Cellsmentioning
confidence: 99%
“…However, the role of GLP-1 in β-cell autophagy is complex and likely dependent on stress conditions. In a rat model fed with high levels of fructose, GLP-1 analog intervention induced notable inhibition of β cell autophagy and enhanced β cell mass and function (Maiztegui et al, 2017). The detailed molecular regulation of the autophagy system in β cells via GLP-1 receptor signaling requires further investigation.…”
Section: Glp-1-related Autophagymentioning
confidence: 99%
“…It has been postulated that impairment in glucose metabolism in the liver is one of the earliest reactions to increased flow and availability of fructose [5,[32][33][34]. We previously demonstrated that three weeks-FRD fed rats developed changes in liver glucose and lipid metabolism paralleling endocrine dysfunction (hyperinsulinemia, hyperleptinemia, higher plasminogen activator inhibitor-1 and lower adiponectin levels) and an insulin resistant state [14][15][16][17][18][19][20]. These rats also show increased oxidative stress markers in the liver and pancreatic islets [14,15,20].…”
Section: Discussionmentioning
confidence: 93%
“…We previously showed that normal rats fed a fructose-rich diet (FRD) for three weeks developed changes in glucose and lipid metabolism together with endocrine dysfunction (hyperinsulinemia, hyperleptinemia, higher plasminogen activator inhibitor-1 and lower adiponectin levels) and an insulin resistant (IR) state [14][15][16][17][18][19][20]. All these changes suggest a complex multi-organ function compromise in animals fed a FRD: adipose tissue (evidenced by increased free fatty acids levels), liver (suggested by several alterations of carbohydrate metabolism and triglyceride levels), and endocrine pancreas (since hyperinsulinemia together with impaired glucose tolerance indicate β-cell functional compromise unable to cope with the enhanced demand for insulin due to IR).…”
Section: Introductionmentioning
confidence: 99%